1996
DOI: 10.1071/rd9960195
|View full text |Cite
|
Sign up to set email alerts
|

ACTH-like bioactivity and immunoactivity in fetal lamb pituitaries at 0.65 and 0.95 gestation

Abstract: We wished to determine if the concentration of bioactive ACTH-like activity increased during development and if there was heterogeneity in ovine fetal anterior pituitary ACTH activity as measured by bioassay and radioimmunoassay (RIA). We obtained anterior pituitaries from eight sheep fetuses (four at 0.65 and four at 0.95 gestation; term 145 +/- 5 days) and extracted and homogenized them in ice-cold 5N acetic acid, 0.3% phenylmethanesulfonyl fluoride (PMSF) and 0.2% BSA. Fractionation of each pituitary extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(Fora et al. ) reported that ovine fetal anterior pituitary cells exhibit a progressive decline in ACTH 1–39 release in response to CRH, while AVP‐induced ACTH release increases. This is supported by the findings of Lu et al., () that CRH binding sites in the anterior pituitary declined during late gestation in the ovine fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fora et al. ) reported that ovine fetal anterior pituitary cells exhibit a progressive decline in ACTH 1–39 release in response to CRH, while AVP‐induced ACTH release increases. This is supported by the findings of Lu et al., () that CRH binding sites in the anterior pituitary declined during late gestation in the ovine fetus.…”
Section: Discussionmentioning
confidence: 99%
“…During this maturational process, there is increased expression of the major ACTH secretagogue, corticotropin-releasing hormone (CRH) in the hypothalamic paraventricular nucleus (PVN) as well as increased expression of the ACTH precursor, proopiomelanocortin (POMC) in the anterior pituitary Challis 1995a, 1997;Myers and Myers 2000). In addition, there is a noted increase in the processing of POMC to ACTH in anterior pituitary corticotrophs that translates to an enhanced bioactivity of fetal plasma immunoreactive ACTH and mature, bioactive ACTH 1-39 (Castro et al 1993;Carr et al 1995;Zehnder et al 1995;Fora et al 1996;Bell et al 1998). These maturational changes in the PVN and anterior pituitary are accompanied by the increased adrenocortical expression of steroidogenic enzymes resulting in the increased cortisol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, one study found that ACTH-positive cells have different staining patterns in the foetal and adult pars distalis and pars intermedia, and have specific temporal patterns of expression in different sites of the pituitary (Perry et al, 1985). However, no selective increase in ACTH-like activity in the anterior pituitary at late gestation was observed using bioassay and radioimmunoassay methods (Fora et al, 1996). Another study found that isolated ACTH-cells first appeared at the boundaries where pars intermedia cells migrated towards the pituitary anterior lobe (Altukhova et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…As the endogenous cortisol concentration is the best available bioassay of endogenous ACTH action, it seems likely that much of the immunoreactive ACTH present in both experimental models is not bioactive. The presence of immunoreactive, ACTH-related peptides with corticotropic, unchanged or anticorticotropic biological activity has been demonstrated in plasma and pituitaries of intact fetuses [10, 23, 34, 35, 36, 37, 38, 39, 40, 41]and it has been speculated that this immunoreactivity may correspond to high molecular weight (MW) ACTH precursors [20, 38, 42, 43]. We have previously demonstrated that the HPD fetus has normal concentrations of both low and high MW ACTH-containing peptides by chromatography [13]and by two site immunoradiometric assays at days 130–140 GA [38, 44]and we now report an apparently identical biological scenario in intact fetuses using a radioimmunoassay that appears to preferentially bind low MW ACTH-immunoreactive species (our unpublished data based on assay of gel chromatography eluates from fetal plasma).…”
Section: Discussionmentioning
confidence: 99%